INCIDENCE OF DEMENTIA IN ADULTS WITH CEREBRAL PALSY: A UK COHORT STUDY. (16th November 2018) - Smith, K; Peterson, M; Victor, C; Ryan, J
Abstract: Researchers have previously hypothesised that ageing with cerebral palsy (CP) may be associated with an increased risk of developing dementia. However no study has yet formally investigated this proposition while accounting for important morbidities such as intellectual disabilities (ID) or epilepsy. We used a United Kingdom primary care database as our data source (CPRD Gold). Data for 1, 705 adults with CP (age range 18–89) and 5, 115 age, sex and general practice matched controls without CP was extracted from the database. Dementia was defined by read codes. We used stratified Cox Proportional Hazards Regression analyses to determine incidence of dementia. In total there were 51 cases of incident dementia over follow-up. There was no significant difference in the risk of developing dementia between people with CP and those without CP (HR 1.40, 95% CI 0.58–3.40). We then repeated our analysis comparing those with CP and either ID or epilepsy with adults without CP. Those with ID co-morbidity had a higher risk of developing dementia than people with no CP (HR 7.11, 95% CI 1.38–36.75) as did those with CP and epilepsy (HR 12.0, 95% CI 1.34–107.36). Results suggest that only those people with CP and ID or epilepsy are more likely to develop dementia. This suggests that the previously speculated link between CP and dementia may be due to other neurologic or intellectual co-morbidities rather than as a direct effect of CP; however, more work is needed to confirm this link and the mechanisms underlying it.